2017
DOI: 10.1016/j.engstruct.2017.08.016
|View full text |Cite
|
Sign up to set email alerts
|

Investigations of elastic vibration periods of reinforced concrete moment-resisting frame systems with various infill walls

Abstract: The fundamental period of vibration is a crucial characteristic in assessing the dynamic performance of reinforced concrete (RC) buildings because it is not only directly related to the mass and stiffness of the structure, but also to the lateral actions applied, e.g. earthquakes and winds. In this study, the RC moment-resisting frame (MRF) systems designed under gravity and wind loading have been evaluated by utilising 3D FE modelling incorporating eigen-analysis to obtain the elastic periods of vibration. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 40 publications
(85 reference statements)
1
1
0
Order By: Relevance
“…They found that periods of vibration of bare frames reasonably agrees with codes formulas by disregarding contributions of infills' stiffness towards the structural systems. On the other hand, the proposed formulas for RC MRF buildings with un-cracked infills agree well with most cited experimentally based formulas and some numerically based ones [14].…”
Section: Comparison Between Numerical Analyses Results and Code Formulassupporting
confidence: 83%
“…They found that periods of vibration of bare frames reasonably agrees with codes formulas by disregarding contributions of infills' stiffness towards the structural systems. On the other hand, the proposed formulas for RC MRF buildings with un-cracked infills agree well with most cited experimentally based formulas and some numerically based ones [14].…”
Section: Comparison Between Numerical Analyses Results and Code Formulassupporting
confidence: 83%
“…In the study, it is suggested to establish and analyse numerical models of both single high-rise buildings and 4 high-rise buildings for a safe design, and to adopt the envelope value in the seismic design of such buildings. Balhawi and Zhang (2019) investigated to vibration periods of tall reinforced concrete office buildings. In this study, RC frame-shear wall systems designed under gravity and wind loadings have been evaluated by utilising 3D FE modelling incorporating eigen-analysis to obtain the elastic periods of vibration.…”
Section: Introductionmentioning
confidence: 99%
“…Almost all the previous developed models give direct relations of the 1418 fundamental vibration period to buildings height. However, it was shown that previous simple models resulted in significantly large variations in predictions [17][18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%